Screening of Fungi for Biological Control of a Triatomine Vector of Chagas Disease: Temperature and Trypanosome Infection as Factors. - Aline R M Garcia; Adriana de Paula Rocha; Camila C Moreira; Silma L Rocha; Alessandra A Guarneri; Simon L Elliot (Public Library of Science (PLoS), 2016)
Entomopathogenic fungi have been investigated as an alternative tool for controlling various insects, including triatomine vectors of the protozoan Trypanosoma cruzi, the etiological agent of Chagas disease. Here we tested the pathogenicity and virulence of ten isolates of the fungi Metarhizium spp. and Beauveria bassiana against Rhodnius prolixus and found all of the isolates to be virulent. We used two isolates (URPE-11 Metarhizium anisopliae and ENT-1 Beauveria bassiana) for further screening based on their prolific sporulation in vitro (an important property of fungal biopesticides). We characterized their virulences in a dose-response experiment and then examined virulence across a range of temperatures (21, 23, 27 and 30°C). We found isolate ENT-1 to maintain higher levels of virulence over these temperatures than URPE-11. We therefore used B. bassiana ENT-1 in the final experiment in which we examined the survival of insects parasitized with T. cruzi and then infected with this fungus (once again over a range of temperatures). Contrary to our expectations, the survival of insects challenged with the pathogenic fungus was greater when they had previously been infected with the parasite T. cruzi than when they had not (independent of temperature). We discuss these results in terms of aspects of the biologies of the three organisms. In practical terms, we concluded that, while we have fungal isolates of potential interest for development as biopesticides against R. prolixus, we have identified what could be a critical problem for this biological tool: the parasite T. cruzi appears to confer a measure of resistance to the insect against the potential biopesticide agent so use of this fungus as a biopesticide could lead to selection for vector competence.